The Effect of Fraud Pentagon and F-Score Model in Detecting Fraudulent Financial Reporting in Indonesia - Putra, Ardhi Nugraha; Dinarjito, Agung (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 16 No 2 (2021), 2021)
This study analyzes the effect of fraud pentagon and the efficacy of the F-score model in detecting fraudulent financial reporting in Indonesia. The sample used is the company’s annual report subject to Financial Service Authority (OJK) sanctions and a twofold comparative annual study from companies not subject to sanctions in the same reporting year and industry type. The sample was selected using a purposive sampling method. The data was analyzed using the logistic regression analysis. The test results prove that pressure, opportunity, and rationalization in the fraud pentagon can be used to detect bogus financial reporting. The results reveal that the F-score model is unsuitable for hypothesis testing; consequently, some variables should be eliminated. Therefore, the F-score model has limited usefulness in detecting counterfeit financial reporting in Indonesia. Keywords:  F-Score, accounting fraud, fraud detection, fraud pentagon, fraudulent financial reporting